2005
DOI: 10.1128/jvi.79.14.8894-8903.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Human Metapneumovirus Lung Infection in BALB/c Mice and Cotton Rats

Abstract: Human metapneumovirus (hMPV) is a newly described member of the Paramyxoviridae family causing acute respiratory tract infections, especially in young children. We studied the pathogenesis of this viral infection in two experimental small animal models (BALB/c mice and cotton rats). Significant viral replication in the lungs of both animals was found following an intranasal challenge of 10 8 50% tissue culture infectious doses (TCID 50 ) and persisted for <2 and <3 weeks in the case of cotton rats and mice, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(151 citation statements)
references
References 49 publications
10
140
1
Order By: Relevance
“…Endpoints used cytopathic effect on the cell monolayers. Virus titers were reported as Log 10 50% tissue culture infectious dose per milliliter of culture supernatant or per gram of lung (Log 10 TCID 50 /ml or Log 10 TCID 50 /g) [10]. TCID 50 was calculated by the method of Reed and Muench.…”
Section: Cell Line and Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Endpoints used cytopathic effect on the cell monolayers. Virus titers were reported as Log 10 50% tissue culture infectious dose per milliliter of culture supernatant or per gram of lung (Log 10 TCID 50 /ml or Log 10 TCID 50 /g) [10]. TCID 50 was calculated by the method of Reed and Muench.…”
Section: Cell Line and Virusmentioning
confidence: 99%
“…Its ability to co-infect with other respiratory infectious agents, including RSV and pneumococci [14,27], combined with its relatively slow replication in cell culture likely accounted for its ability to escape isolation until 2001. Various animal models have been utilized to study hMPV infection including mice, hamsters, and several species of primates [10,12,13,23]. Recent studies indicate that infection of cotton rats with hMPV is associated with efficient viral replication in the lung and reproducible pulmonary pathology [10,28,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unusual biphasic growth curve has not been observed for HMPV (or for that matter, RSV) in any other animal model by these or other investigators, and thus the biological significance is unclear. In addition to Alvarez et al [1,2], Hamelin et al [6] observed that the lung virus peaks somewhat earlier at day 5 p.i. in both BALB/c mice and cotton rats, an observation that is supported by Darniot et al [4].…”
Section: Mouse Model (Balb/c)mentioning
confidence: 84%
“…Several animal species have been determined to be permissive for HMPV infection [1,4,6,9,10,12,18,23,27]. These models, which are described in more detail below, include small animals such as mice, cotton rats, hamsters, guinea pigs, ferrets, and primates, including chimpanzees, rhesus macaques and African green monkeys.…”
Section: Introductionmentioning
confidence: 99%